Digest of U-Report surveys: 1st quarter of 2025 (career guidance in the school environment, student participation in student self-government bodies, educational needs of students) - Demchuk V. S.; Hupalo A. I. (Український соціум)
The results of surveys of the innovative youth project U-Report are shown for January – March 2025: career guidance in the school environment, student participation in student self-government bodies, educational needs of students.